Behind sleepy eyes: Implications of sleep loss for organizations and employees - Budnick, Christopher J.; Barber, Larissa K. (Translational Issues in Psychological Science, 2015)
Sleep loss and daytime sleepiness are common experiences for employees across many occupations. Although researchers commonly focus on the detrimental effects of sleep issues for attention and vigilance during task performance, we review research that examines how sleep issues influence interpretations of, and interactions in, the work environment. This review begins by differentiating between sleep loss and sleepiness. We then highlight how sleep issues can negatively bias the interpretation of environmental information and result in aggressive responding. We also examine how sleep issues impair self-regulatory ability and contribute to workplace deviance. After each section, we discuss the implications of these findings for the work environment. A closer examination of sleep’s influence on workplace interactions can spur a beneficial discussion for researchers across a variety of disciplines and employees across all organizational levels. (PsycInfo Database Record (c) 2022 APA, all rights reserved)
Place: US
Keywords: Aggressive Behavior; Employee Productivity; Health; Occupations; Organizations; Personnel; Self-Control; Sleep Deprivation; Sleepiness; Stress; Working Conditions; dept.psy